Montenegro : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Montenegro. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2010 Article IV Consultation highlights that Montenegro has been hard hit by the global financial crisis. Contagion and concerns about the robustness of the banking system have triggered large deposit withdrawals and a credit crunch. Moreover, the unwinding of the real estate boom has generated strong negative wealth effects that depressed demand. The authorities have taken wide-ranging measures to stabilize the financial system and rekindle lending activity. Foreign parents have also stepped in with substantial liquidity infusion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet